2013
DOI: 10.18172/cig.1122
|View full text |Cite
|
Sign up to set email alerts
|

El niño driven climate variability and drainage anomalies in Patagonian region Argentina

Abstract: (3) Faculty of A g ro n o m y, Buenos A i res University (4) Wa t e r R e s o u rces Sub Secre t a ry, Serrano 669 (1414) Buenos A i res, A r g e n t i n a e-mail: olga@mpero . c y t . e d u . a r ABSTRACT: Forecasting of interannual and seasonal variability of hydrological processes is very important when planification of water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have reported significant relationships between ENSO and mean annual discharges of the Neuquén River (Scarpati et al, 2001;Seoane et al, 2005). However, the comparison between pre-whitened variations of both ENSO and October-June Neuquén River flow (both observed and reconstructed records) reveals positive, but not statistically significant correlations between these variables.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported significant relationships between ENSO and mean annual discharges of the Neuquén River (Scarpati et al, 2001;Seoane et al, 2005). However, the comparison between pre-whitened variations of both ENSO and October-June Neuquén River flow (both observed and reconstructed records) reveals positive, but not statistically significant correlations between these variables.…”
Section: Discussionmentioning
confidence: 94%